2013
DOI: 10.1186/1755-8794-6-42
|View full text |Cite
|
Sign up to set email alerts
|

Gene profiling suggests a common evolution of bladder cancer subtypes

Abstract: BackgroundBladder cancer exists as several distinct subtypes, including urothelial carcinoma (UCa), squamous cell carcinoma (SCCa), adenocarcinoma and small cell carcinoma. These entities, despite showing distinct morphology and clinical behavior, arise from the urothelial lining and are often accompanied by similar precursor/in situ findings. The relationship between these subtypes has not been explored in detail.MethodsWe compared gene expression analysis of the two most common subtypes of bladder cancer, UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…A previous study explored the relationship between UCCs and squamous cell carcinomas (SCCa) of the bladder and showed UCCs to express very few unique dysregulated genes and share the majority of its dysregulated genes relative to normal urothelium with SSCa (Hansel et al 2013). In contrast, SCCa, while expressing many genes common with UCCs, express many more dysregulated genes common in SCCa arising at other sites.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study explored the relationship between UCCs and squamous cell carcinomas (SCCa) of the bladder and showed UCCs to express very few unique dysregulated genes and share the majority of its dysregulated genes relative to normal urothelium with SSCa (Hansel et al 2013). In contrast, SCCa, while expressing many genes common with UCCs, express many more dysregulated genes common in SCCa arising at other sites.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous cell carcinoma is defined by the presence of intercellular bridges or keratinization and may be present in up to 40% of invasive urothelial carcinomas [63][64][65][66]. It is almost never associated with human papillomavirus infection, with the rare exception of some cases with a basaloid morphology [67,68].…”
Section: Invasive Urothelial Carcinoma With Divergent Differentiationmentioning
confidence: 99%
“…Many studies have shown that the protein expression of the ADH1B gene is downregulated in many tumors. 47 , 48 Compared with levels in normal tissues, the mRNA levels of ADH1B in colorectal cancer tissues were low. 49 The risk of residual lesions in patients with high-grade ovarian cancer after cytoreductive surgery is closely related to the high expression of ADH1B.…”
Section: Discussionmentioning
confidence: 93%